2003
DOI: 10.1097/00006676-200304000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Epicatechin Against the Toxic Effects of Streptozotocin on Rat Pancreatic Islets: In Vivo and in Vitro

Abstract: EC appears to be helpful in protecting pancreatic islets against exposure to STZ in both in vivo and in vitro systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 35 publications
4
62
0
2
Order By: Relevance
“…Considering that, in a separate pharmacological study, each extract (leaf, stem, root and fruit) elicited a range of in vitro anti-diabetic activities (Martineau et al, 2006), it is interesting that all the identified classes of phenolic compounds, chlorogenic acid, quercetin derivatives, procyanidins and anthocyanins, have demonstrated anti-diabetic potential in vitro and in vivo (Hemmerle et al, 1997;Rodriguez de Sotillo and Hadley, 2002;Kim et al, 2003;Tsuda et al, 2003;Pinent et al, 2004;Ajay et al, 2005;Coskun et al, 2005;Dias et al, 2005;Jayaprakasam et al, 2006 …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Considering that, in a separate pharmacological study, each extract (leaf, stem, root and fruit) elicited a range of in vitro anti-diabetic activities (Martineau et al, 2006), it is interesting that all the identified classes of phenolic compounds, chlorogenic acid, quercetin derivatives, procyanidins and anthocyanins, have demonstrated anti-diabetic potential in vitro and in vivo (Hemmerle et al, 1997;Rodriguez de Sotillo and Hadley, 2002;Kim et al, 2003;Tsuda et al, 2003;Pinent et al, 2004;Ajay et al, 2005;Coskun et al, 2005;Dias et al, 2005;Jayaprakasam et al, 2006 …”
Section: Figurementioning
confidence: 99%
“…Phenolic compounds were emphasised because of their abundance in closely related Vaccinium species (Witzell et al, 2003) and because many different phenolics have demonstrated in vivo anti-diabetic activities (Kim et al, 2003;Coskun et al, 2005). Using a metabolomics-based approach for preliminary compound identification and reference standards for confirmation, chemical profiles for each organ were determined and quantitative comparisons conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Generation of free radicals has been proposed to be a major mechanism involved in the streptozotocin (STZ) cytotoxicity. STZ is frequently used to induce diabetes mellitus in experimental animals through its toxic effects on pancreatic β-cells (Yamagishi et al, 2001;Stefek et al, 2002;Kalendar et al, 2002;Kim et al, 2003). The cytotoxic action of STZ is associated with the generation of reactive oxygen species causing oxidative damage (Szkudelski, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Outras São vários os mecanismos de ação de plantas hipoglicemiantes, como a estimulação da secreção de insulina das células beta das ilhotas pancreáticas ou a inibição da degradação de insulina [46]; adrenomimetismo, bloqueio do canal de potássio na célula beta pancreática [47]; redução da resistência à insulina [46]; regeneração e reparo das células beta pancreáticas [48]; aumento do número de células nas ilhotas pancreáticas [48]; estimulação da secreção de insulina [47]; estimulação da glicogêneses e glicólise hepática [50]; efeito protetor na destruição de células beta pancreáticas [51]; diminuição da atividade do cortisol [52]; inibição da alfa-amilase [53]; prevenção do estresse oxidativo que está relacionado com a disfunção da célula beta pancreática [54].…”
Section: Figura 2 -Distribuição Percentual De Pessoas Que Conhecem Ouunclassified